Strategi Komunikasi INEWS TV Dalam Menjalin Kerjasama Sponsorship Pada Program Koalisi Tawa - Enzelita, Desy; Huwae, George Nicholas (Peneliti.net, 2024)
Television is a medium that business people often use to market their products. On the other hand, television media will receive financial support to run television programs. iNews TV is one of the television media that exists at the national level. iNews TV provides news programs and non-news programs, one of which is the Tawa Coalition program. This research aims to find out iNews TV's communication strategy in establishing sponsorship cooperation and how sponsorship is implemented in the Tawa Coalition program on iNews television. The method used in the research is the descriptive qualitative method. Data was obtained through observation and in-depth interviews with staff at iNews TV. The results show that iNews TV applies three communication strategy theories, namely Pull Strategy, where iNews TV conducts research in designing the Tawa Coalition program airing schedule to see which schedule will provide high performance so that it is easier to reach the audience; Push Strategy which is a communication strategy carried out in the internal environment of iNews TV, in this case the role of the Implementer is needed as a communication bridge between the Sales team and the Production team in implementing sponsorship benefits, and Profile Strategy where iNews TV maintains its image by improving program performance to open up opportunities for sponsorship cooperation. The sponsorship planning strategies carried out are adjusting the target audience of the program and brand (Target Audience Reach), changing the theme of the program and the product to be advertised (Compatibility with Company's or Brand Positioning), and packaging the message that the brand wants to convey in the form of sponsorship benefits (Message Capacity). The sponsorship benefits are implemented through the Pre-Production, Production, and Post-Production stages. At each stage, iNews TV provides a material review to the client to see if the benefit of sponsorship is following what the client wants.